A long journey to COVID-19 in obese patients - Fatima Kh. Dzgoeva; Olga A. Radaeva; Madina I. Asadulaeva; Elizaveta M. Vardanyan; Diana S. Rafikova; Ekaterina A. Troshina (LLC "MEDIAFORMAT", 2021)
The paper reports clinical cases of obese patients who have had severe coronavirus infection (COVID-19): one case of damage to the gastrointestinal tract, and one case of neurological manifestation worsening (possible cognitive impairment). Assessment and therapeutic treatment of obese patients is challenging in terms of high thromboembolic complication rate. When choosing comprehensive treatment, dietary care and drug therapy, the improvement was observed in the form of gradual regression of disorders and further body weight reduction, which had a potential to affect the risk of complications, and to improve the overall quality of life of the patients.